The Legality Issue of the Financing Contract at the Sharia Rural Banks (BPRS) and the Solution in Sharia Agreement Law Perspective - Isdian Anggraeny; Wardah Dinnar Rahmadanti (University of Udayana, 2020)
Sharia-based financing institutions are currently experiencing developments in the financial industry. Sharia financing provided by the BPRS is one of the ways that can be used by the community to meet their daily needs or manage their business. The use of financing certainly has the risk of default and execution of collateral which of course will be detrimental to the creditors (BPRS). Various financing problems are generally caused by the financing process that does not pay attention to legal provisions, especially sharia contract law and guarantee law. Taking the theme: